2005
DOI: 10.1021/bi052202j
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Topology of Human ASBT (SLC10A2) Determined by Dual Label Epitope Insertion Scanning Mutagenesis. New Evidence for Seven Transmembrane Domains

Abstract: The membrane topology of the human apical sodium-dependent bile acid transporter (hASBT) remains unresolved. Whereas N-glycosylation analysis favors a 7 transmembrane (TM) model, membrane insertion scanning supports a 9TM topology. In order to resolve this controversy, we used dual label epitope insertion to systematically examine the topological framework of hASBT. Two distinct epitopes, hemagglutinin (HA) and FLAG, were individually inserted by inverted PCR mutagenesis at strategic positions along the hASBT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 30 publications
0
48
0
Order By: Relevance
“…Cysteine Scan of EL1-As predicted by our topology model (25,28), residues spanning Val-99 -Ser-126 form the EL1 protein region, which exhibits high sequence conservation among a range of evolutionarily diverse species (Fig. 1).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Cysteine Scan of EL1-As predicted by our topology model (25,28), residues spanning Val-99 -Ser-126 form the EL1 protein region, which exhibits high sequence conservation among a range of evolutionarily diverse species (Fig. 1).…”
Section: Resultsmentioning
confidence: 92%
“…This uptake period ensures linear steady-state kinetics in conjunction with an optimal signal-to-noise ratio for subsequent [ 3 H]TCA analysis via liquid scintillation counting (22,23,28). Uptake was halted by a series of washes with ice-cold Dulbecco's phosphate-buffered saline, pH 7.4, containing 0.2% fatty acid free bovine serum albumin and 0.5 mM TCA.…”
Section: Materials-[mentioning
confidence: 99%
“…A model with nine-TM segments has been proposed based on a prediction method using HMMTOP and in vitro translation analysis, 23) while scanning analyses of epitope and glycosylation site insertions suggested a seven-TM model. 22,26) Moreover, a novel seven-TM model, in which TM6 and TM7 of the nine-TM model are associated with the plasma membrane at the extracellular surface, is proposed for human SLC10A1. 25) Cys 51 in Slc10a2 is located just at the boundary between the first TM segment and the first intracellular loop in both the seven-TM and nine-TM models (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While precise information about the substrate binding domains of hASBT are not available yet, its structural and functional determinants have been studied using various biophysical methods [36][37][38][39][40] . These studies have indicated that hASBT exhibits a seven transmembrane (7 TM) topology similar to NTCP.…”
Section: Biology Of Asbtmentioning
confidence: 99%